2013
DOI: 10.3109/1547691x.2013.867913
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of anthrax lethal factor on rat liver

Abstract: Bacillus anthracis, the causative agent of anthrax, has become an increasingly important scientific topic due to its potential role in bioterrorism. The lethal toxin (LT) of B. anthracis consists of lethal factor (LF) and a protective antigen (PA). This study investigated whether only lethal factor was efficient as a hepatotoxin in the absence of the PA. To achieve this aim, LF (100 mg/kg body weight, dissolved in sterile distilled water) or distilled water vehicle were intraperitoneally injected once into adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…19 Previous studies have revealed that anthrax induces liver damage; invasions of bacterium B. anthracis have been observed frequently in the liver of infected patients [20][21][22] and animals. 15,23,24 These results prompted us to investigate whether coagulant factor defects are associated with LT-induced liver damage. Herein, we determined that LT challenges induce toxicity toward hepatic cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous studies have revealed that anthrax induces liver damage; invasions of bacterium B. anthracis have been observed frequently in the liver of infected patients [20][21][22] and animals. 15,23,24 These results prompted us to investigate whether coagulant factor defects are associated with LT-induced liver damage. Herein, we determined that LT challenges induce toxicity toward hepatic cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%